2018
DOI: 10.1111/den.13184
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Gastroenterological Endoscopy in Patients Undergoing Antithrombotic Treatment: 2017 Appendix on Anticoagulants Including Direct Oral Anticoagulants

Abstract: In 2012, the Japan Gastroenterological Endoscopy Society published "Guidelines for Gastroenterological Endoscopy in Patients Undergoing Antithrombotic Treatment" concerning thromboembolism associated with antithrombotic therapy withdrawal. Since then, physicians have started prescribing oral anticoagulants, creating a need for standards reflecting their use in clinical practice. Therefore, new findings regarding anticoagulants are included in this appendix. However, the evidence levels are low for many stateme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
192
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(196 citation statements)
references
References 36 publications
3
192
0
1
Order By: Relevance
“…After evaluating both risks, a decision should be made regarding whether the patient should continue to take the medication. If drug discontinuation is recommended, optimal timing for drug discontinuation and resumption must be carefully evaluated . The risk of thromboembolism differs depending on the status of the patient’s underlying disease, and the type and time of placement of artificial valves or stents.…”
Section: Indication For Endoscopic or Surgical Treatmentmentioning
confidence: 99%
“…After evaluating both risks, a decision should be made regarding whether the patient should continue to take the medication. If drug discontinuation is recommended, optimal timing for drug discontinuation and resumption must be carefully evaluated . The risk of thromboembolism differs depending on the status of the patient’s underlying disease, and the type and time of placement of artificial valves or stents.…”
Section: Indication For Endoscopic or Surgical Treatmentmentioning
confidence: 99%
“…Recently published supplementary issue of JGES guidelines for management of patients taking anticoagulants suggests the possibility of continuation of warfarin instead of heparin bridging therapy during high‐bleeding‐risk endoscopic procedures because many studies showed a high incidence of delayed bleeding after gastric ESD in patients received heparin bridging therapy (10.8–61.5%; Table ) …”
Section: Adverse Events Related To Gastric Esdmentioning
confidence: 99%
“…For antiplatelet drugs, some studies have shown that the continuous or discontinued use of aspirin does not increase the incidence of postoperative bleeding in patients undergoing ESD . Therefore, guidelines recommend continuous aspirin use during gastric ESD to reduce the incidence of thrombotic events . Other studies indicate that taking a single antiplatelet drug is not associated with post‐ESD bleeding, but for those receiving dual antiplatelet therapy the incidence of hemorrhage is significantly increased .…”
Section: Risks Of Bleeding After Gastric Esdmentioning
confidence: 99%
“…When analyzing the risks of hemorrhage during heparin replacement therapy, Dong et al performed a meta‐analysis that included 10 540 patients from 16 studies, showing that heparin replacement therapy could increase the incidence of post‐ESD bleeding. Therefore, in 2017 guidelines the Japan Gastroenterological Endoscopy Society no longer recommend heparin replacement therapy for patients undergoing endoscopic surgery with anticoagulants …”
Section: Risks Of Bleeding After Gastric Esdmentioning
confidence: 99%
See 1 more Smart Citation